2018
DOI: 10.1002/jlb.5a0817-324r
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin surges are linked to acute episodes of the systemic capillary leak syndrome (Clarkson disease)

Abstract: Since ADM has established hypotensive effects, differentiating between these dual actions of ADM is crucial for therapeutic applications aimed at more common diseases associated with increased ADM levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 35 publications
(92 reference statements)
2
35
0
1
Order By: Relevance
“…So far, a predictive value of individual MR-proADM measurements has been found in ischemic and congestive heart disease [33][34], after cardiac surgery [8], in sepsis [35], in pneumoniae [13,36] and in other ARDS-related conditions [37]. Despite the low number of cases affected by serious viral pathologies included in previous studies [14,38], we believe that a similar effect can be hypothesized in the context of cohorts of COVID-19 patients. It is hence possible, as already proposed in the context of sepsis [16], that the use of this biomarker could help either to anticipate the escalation of therapy in patients at risk of treatment failure or to suggest a faster discharge of patients with a low risk of unfavorable evolution.…”
Section: Discussionmentioning
confidence: 62%
“…So far, a predictive value of individual MR-proADM measurements has been found in ischemic and congestive heart disease [33][34], after cardiac surgery [8], in sepsis [35], in pneumoniae [13,36] and in other ARDS-related conditions [37]. Despite the low number of cases affected by serious viral pathologies included in previous studies [14,38], we believe that a similar effect can be hypothesized in the context of cohorts of COVID-19 patients. It is hence possible, as already proposed in the context of sepsis [16], that the use of this biomarker could help either to anticipate the escalation of therapy in patients at risk of treatment failure or to suggest a faster discharge of patients with a low risk of unfavorable evolution.…”
Section: Discussionmentioning
confidence: 62%
“…In particular, they suggested that the cooperation of these vasoactive peptides might be necessary to counterbalance the vasodilatory activity of bradykinin and to terminate the attacks. Recently, Xie and collegaues (37), confirmed these data in acute Systemic Capillary Leak Syndrome (SCLS), characterized by abrupt and transient episodes of hypotensive shock and edema due to plasma leakage into peripheral tissues.…”
Section: Discussionmentioning
confidence: 80%
“…ADM could act as an endogenous immunomodulatory factor, with predominant anti-inflammatory effects (35). It is produced in many types of tissue, but the endothelium (36) and the monocytes (37) are the principal source, in particular in response to proinflammatory cytokines (38). ADM reduces endothelial hyper-permeability and is an apoptosis survival factor (39).…”
Section: Discussionmentioning
confidence: 99%
“…Hence a key aim of this study focused on the comparison of biomarker and clinical score performance according to the location of initial infection development, following activation of an in-hospital sepsis code. Based on recent publications, the use of MR-proADM was of especial interest within our investigation, with previous studies showing elevated concentrations resulting from increased levels of microcirculatory and endothelial damage, resulting in the early stages of subsequent organ dysfunction [26][27][28][29]. The use of a biomarker to identify developing microcirculatory damage may contribute significant information following the activation of a local, in-hospital sepsis code.…”
Section: Discussionmentioning
confidence: 99%